A transcription factor network specifying inhibitory versus excitatory neurons in the dorsal spinal cord - Borromeo, M. D. (2015)
The proper balance of excitatory and inhibitory neurons is crucial for normal processing of somatosensory information in the dorsal spinal cord. Two neural basic helix-loop-helix transcription factors (TFs), Ascl1 and Ptf1a, have contrasting functions in specifying these neurons. To understand how Ascl1 and Ptf1a function in this process, we identified their direct transcriptional targets genome-wide in the embryonic mouse neural tube using ChIP-Seq and RNA-Seq. We show that Ascl1 and Ptf1a directly regulate distinct homeodomain TFs that specify excitatory or inhibitory neuronal fates. In addition, Ascl1 directly regulates genes with roles in several steps of the neurogenic program, including Notch signaling, neuronal differentiation, axon guidance and synapse formation. By contrast, Ptf1a directly regulates genes encoding components of the neurotransmitter machinery in inhibitory neurons, and other later aspects of neural development distinct from those regulated by Ascl1. Moreover, Ptf1a represses the excitatory neuronal fate by directly repressing several targets of Ascl1. Ascl1 and Ptf1a bind sequences primarily enriched for a specific E-Box motif (CAGCTG) and for secondary motifs used by Sox, Rfx, Pou and homeodomain factors. Ptf1a also binds sequences uniquely enriched in the CAGATG E-box and in the binding motif for its co-factor Rbpj, providing two factors that influence the specificity of Ptf1a binding. The direct transcriptional targets identified for Ascl1 and Ptf1a provide a molecular understanding of how these DNA-binding proteins function in neuronal development, particularly as key regulators of homeodomain TFs required for neuronal subtype specification.